Analisis Faktor Penyebab Terjadinya Duplikasi Nomor Rekam Medis di Puskesmas Mayang Jember - Yemima Septa Claudia Simamora; Veronika Vestine; Gamasiano Alfiansyah; Selvia Juwita Swari (Indonesian Journal Publisher, 2024)
The duplication incident that occurred at the Mayang Jember Health Center was one medical record number owned by more than one different patient. Duplications found were 23 files with a percentage of 2.88% in January-March 2023. This research is to identify the factors that cause duplication of medical record numbers based on ability, motivation and opportunity variables. This type of research is qualitative with the research subjects being the person in charge of medical records, medical record officers and porters. Data collection techniques using interviews, observation, documentation and prioritization of the causes of problems using scoring and improvement efforts by brainstorming. The results of the study found that the priority cause of problems using the scoring method is the unavailability of standard operating procedures on medical record numbering. An effort to improve the problem is to recommend Standard Operating Procedures on Medical Record Numbering and conducting socialization related to the clarity of Standard Operating Procedures that have been made.